EFEK ANTIBAKTERI EKSTRAK ETANOL DAUN PANDAN WANGI (Pandanus amaryllifolius Roxb.) SEBAGAI ALTERNATIF BAHAN IRIGASI SALURAN AKAR TERHADAP Staphylococcus aureus (In Vitro) - Cut Nurliza; Nevi Yanti; Fitri Yunita Batubara; Dwi Intan Pratiwi (Cahaya Ilmu Bangsa Institute, 2025)
The use of effective and safe irrigation materials is very important to reduce bacterial growth. The purpose of this study was to determine the KHM and KBM values of ethanol extract of pandan wangi leaves with concentrations of 100%, 50%, 25%, 12.5%, 6.25%, 3.125%, 1.56% against Staphylococccus aureus bacteria as an alternative root canal irrigation material. This type of research is experimental with Posttest Only Control Group Design. Thick extract was produced from 1 kg of pandan leaves extracted using 96% ethanol solvent. Then the thick extract is diluted with DMSO and divided into concentrations of 100%, 50%, 25% 12.5%, 6.25%, 3.125%, 1.56% later the ingredients will be tested and replicated 4 times. Determination of KHM and KBM was carried out by dilution method combined with Miles Misra's Drop Plates method. The test results were carried out with Kruskal-Wallis and Pos hoc LSD which obtained significant results of p = 0.001 which means p <0.05, it can be concluded that the ethanol extract of pandan wangi leaves has an antibacterial effect on Staphylococcus aureus with a KHM value at 25% and a KBM value at 50% and when compared to NaOCl, it is found that the 50% extract concentration has a similar ability to NaOCl 2.5% in killing Staphylococcus aureus bacteria.